Attaining sustainable development through poverty alleviation, higher education management and business environment strategies in Nigeria (2008)
Sustainable development is an all inclusive concept which is a function of several factors. Factors that assist sustainable development is higher productivity that increases economic growth rapidly. Where sustainable development is on going, the standard of living in such countries is very high hence most countries desire it. Certain factors aid sustainable development, these include education which provides the necessary skills to increase productivity, poverty alleviation as a factor will empower the people towards increasing the national capital stock, and a good business environment will determine the level of investment in such an economy. This study investigated the concepts of poverty alleviation, higher education management and business environment. It gave the conceptual definitions of the three variables and highlighted indices of under development that showed high population, low productivity, mono export economy and economies dependent on primary production. The tripartite issues in higher education of funding, autonomy and access to education were also discussed. Policy options and solutions were provided at the end of the study.